Carbon / iron sulfide composite negative electrode material and preparation method

The preparation of carbon/ferrous sulfide composite negative electrode material through simplified solvent method solves the problems of cumbersome processes and poor electrochemical performance, and achieves high-efficiency and low-cost preparation technology and excellent electrochemical performance.

CN118908291BActive Publication Date: 2025-04-25XIANYANG VOCATIONAL TECHN COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410959051.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2025-04-25
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

The preparation method and process of the existing carbon/ferrous sulfide composite negative electrode materials are complicated, and the obtained iron sulfide composite negative electrode materials have poor sodium ion electrochemical performance.

Method used

Iron hydroxyl oxide was synthesized by a simple solvent method, and a carbon/hydroxyl iron oxide composite material was obtained by vacuum filtration, and then carbonized at high temperature under the protection of an inert atmosphere to obtain a carbon/ferric sulfide composite negative electrode material.

Benefits of technology

This method simplifies the preparation process, reduces energy consumption and production costs, and significantly improves the electrochemical properties of the materials, including improved volume expansion effects and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908291B_ABST
    Figure CN118908291B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon / iron sulfide composite negative electrode material and a preparation method. An iron source is added to deionized water and stirred and dissolved to obtain a solution A; solution A is added to an alkaline aqueous solution, stirred and mixed continuously to obtain a mixed solution B; the mixed solution B is aged at a high temperature, then washed and dried to obtain oxyhydroxide; oxyhydroxide is added to a carbon nanosheet solution dissolved in an organic solvent, ultrasonically dispersed and then filtered to obtain a carbon / oxyhydroxide composite material; the carbon / oxyhydroxide composite material and a sulfur source are placed in a tubular furnace together for high-temperature carbonization to obtain a carbon / iron sulfide composite negative electrode material. The carbon / iron sulfide composite material of the present invention belongs to a self-supporting structure, avoids the addition of a binder and conductive carbon black, and while reducing the production cost of the negative electrode material, avoids the influence of additional substances on the electrical properties of the material; effectively improves the volume expansion effect of iron sulfide during the charge and discharge process, and improves its electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery electrode material preparation methods, and specifically relates to a method for preparing a carbon / iron sulfide composite negative electrode material; and also relates to a carbon / iron sulfide composite negative electrode material. Background Art

[0002] At present, due to the abundance of sodium resources and the competitiveness of prices, sodium-ion batteries, as emerging secondary batteries, have significantly improved their performance compared to lithium-ion batteries. However, due to the large size of Na ions, sodium-ion batteries in practical applications still exhibit low cycle stability and slow electrode kinetics. Therefore, it is crucial to develop efficient negative electrode materials for sodium-ion batteries with excellent electrochemical properties. In recent years, a large number of sodium-ion battery negative electrode materials with excellent performance have been reported. Among them, transition metal sulfides have attracted much attention due to their high theoretical specific capacity. Specifically, iron sulfide materials have been widely explored due to their excellent redox reversibility, abundance and cost advantages. For example, the document "Chemical Engineering Journal, 2023, 458: 141354." discloses a method for preparing iron sulfide negative electrode materials by a one-step hydrothermal method. Sodium sulfide nonahydrate and iron powder were mixed and added to a hydrothermal reactor, and the iron sulfide material was obtained at a constant temperature of 125°C for 6 hours. The capacity of the iron sulfide material can reach 400mAh / g at 1A / g, but after 200 cycles, the capacity decayed to 70%, and the first coulombic efficiency was about 61%. However, iron sulfide as a negative electrode material for sodium ion batteries usually has a significant volume expansion effect, resulting in electrode pulverization and electrochemical agglomeration, resulting in a sharp drop in capacity, and also has poor electronic conductivity and sluggish kinetic performance. Therefore, it needs to be compounded with materials with good conductivity and good mechanical properties to improve its performance.

[0003] The patent "CN 117334907 A" discloses a three-dimensional porous carbon-based-selenide / iron sulfide composite material and its application in sodium ion batteries. The obtained composite material can exhibit a reversible capacity of 370 mAh / g. The document "Journal of Alloys and Compounds, 2019, 795: 54-59." discloses a method for preparing a carbon-coated iron sulfide composite negative electrode material, using a syringe needle to add a 1wt% sodium alginate solution to a 2.5wt% ferric chloride hexahydrate aqueous solution and stir for 30 minutes to promote Fe cross-linking gelation. Secondly, the prepared gel is separated from the solution and washed with distilled water several times. Then, the obtained gel is dehydrated to form a 3D alginate aerogel through a freeze-drying process. Third, the aerogel is heated at 800°C for 2 hours under an argon atmosphere, and then the sample is mixed with sublimated sulfur and annealed at 600°C for 2 hours to generate a carbon-coated iron sulfide composite material. The capacity of the obtained material is 395 mAh / g, and the initial coulombic efficiency is 74.2%. The above solution is relatively complicated to prepare and requires multiple carbonization processes, which consumes a lot of energy. At the same time, the obtained material is a powder material, which needs to be combined with a binder and conductive carbon black to prepare an electrode, which increases the cost of electrode production and affects the initial coulombic efficiency of the material.

[0004] Therefore, it is urgent to reduce energy consumption, save costs, simplify the synthesis process, and rationally design carbon / iron sulfide materials with excellent electrochemical properties. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a carbon / iron sulfide composite negative electrode material, aiming to solve the problem that the existing method for preparing a carbon / iron sulfide composite negative electrode material is complicated and the obtained iron sulfide composite negative electrode material has poor sodium ion electrochemical performance.

[0006] The present invention also aims to provide a carbon / iron sulfide composite negative electrode material.

[0007] The first technical solution adopted by the present invention is a method for preparing a carbon / iron sulfide composite negative electrode material, and the specific operating steps are as follows:

[0008] Step 1, adding an iron source to deionized water and stirring the water sufficiently to completely dissolve the iron source to obtain a solution A;

[0009] Step 2, adding solution A to the alkaline aqueous solution, stirring continuously until fully mixed, to obtain a mixed solution B;

[0010] Step 3, aging the mixed solution B at high temperature, then washing the product with deionized water and ethanol, and drying to obtain iron oxyhydroxide;

[0011] Step 4, adding ferric oxyhydroxide to a carbon nanosheet solution dissolved in an organic solvent in a certain proportion, dispersing the mixture uniformly by ultrasonication, and then filtering the mixture to obtain a carbon / ferric oxyhydroxide composite material;

[0012] Step 5, placing the carbon / iron oxyhydroxide composite material and the sulfur source into a tubular furnace, and performing high-temperature carbonization under the protection of an inert atmosphere to obtain a carbon / iron sulfide composite negative electrode material.

[0013] The present invention is also characterized in that:

[0014] In step 1, the iron source includes one or more of ferric chloride hexahydrate, ferric nitrate nonahydrate, and ferrous sulfate.

[0015] In step 1, the amount of the iron source added is 0.01-0.1 mol, and the amount of deionized water is 10-200 mL.

[0016] In step 2, the alkaline aqueous solution includes one or more of potassium hydroxide, sodium hydroxide, and ammonia water.

[0017] In step 2, the concentration of the alkaline aqueous solution is 1-10 mol / L, and the volume of the alkaline aqueous solution is 10-200 mL.

[0018] In step 3, the high temperature is 70-150° C., and the aging time is 24-96 hours.

[0019] In step 4, the mass ratio of iron oxyhydroxide to carbon nanosheets is 1:0.01-0.1.

[0020] In step 4, the carbon nanosheets can be purchased on the market or prepared by oneself.

[0021] Specifically, the present invention can prepare carbon nanosheets by the following method: using graphite paper as a working electrode, a platinum sheet as an inert electrode, and 0.1-2M sulfuric acid as an electrolyte, electrolysis is performed at a voltage of 1-15V, and after the reaction is completed, washing to neutrality to obtain carbon nanosheets.

[0022] In step 4, the organic solvent is one or more of isopropanol, N,N-dimethylformamide, ethanol, and methanol.

[0023] In step 4, the volume of the organic solution is 30-100 mL.

[0024] In step 5, the mass ratio of the carbon / iron oxyhydroxide composite material to the sulfur source is 1:0.5-5.

[0025] In step 5, the sulfur source is one or more of thiourea, sulfur powder, and thioacetamide.

[0026] In step 5, the heating rate in the high-temperature carbonization is 2-10°C / min, the calcination time is 1-5h, and the constant temperature is 400-700°C.

[0027] The second technical solution adopted by the present invention is to use the carbon / iron sulfide composite negative electrode material obtained by the preparation method of the carbon / iron sulfide composite negative electrode material of the present invention, and the carbon / iron sulfide composite negative electrode material as the negative electrode in a sodium ion battery.

[0028] The beneficial effects of the present invention are:

[0029] The iron-based compound of the present invention is low-cost and environmentally friendly, but the material itself has poor electrical conductivity, high irreversible capacity loss, and has a large volume expansion effect. The present invention proposes a method for preparing a carbon / iron sulfide composite negative electrode material, which synthesizes oxyhydroxide iron by a simple solvent method, and then obtains a carbon / iron oxyhydroxide composite material by vacuum filtration, and then performs a sulfurization reaction on it to obtain a carbon / iron sulfide composite negative electrode material. First, the coating structure of carbon nanosheets on iron sulfide is not only conducive to shortening the diffusion path of sodium ions, but also can effectively alleviate the volume expansion effect of iron sulfide during the electrochemical reaction process. Secondly, since the carbon / iron sulfide composite material belongs to a self-supporting structure, the addition of binders and conductive carbon black is avoided, while reducing the production cost of the negative electrode material, the influence of additional substances on the electrical properties of the material is avoided. Therefore, this carbon / iron sulfide composite material can effectively improve the volume expansion effect of iron sulfide during the charge and discharge process and improve its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the carbon / iron sulfide composite negative electrode material prepared in Example 1 of the present invention.

[0031] Figure 2 This is the XRD pattern of the carbon / iron sulfide composite negative electrode material prepared in Example 1 of the present invention.

[0032] Figure 3 This is the cycle performance curve of the carbon / iron sulfide composite negative electrode material prepared in Example 1 of the present invention.

[0033] Figure 4 This is the rate performance curve of the carbon / iron sulfide composite negative electrode material prepared in Example 1 of the present invention.

[0034] Figure 5 This is the cycle performance curve of the carbon / iron sulfide composite negative electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0035] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.

[0036] Example 1

[0037] 0.05 mol of ferric nitrate nonahydrate was added to 100 mL of deionized water and stirred thoroughly to obtain solution A; solution A was then added to 100 mL of 5 mol / L potassium hydroxide solution and stirred continuously to obtain solution B; solution B was aged at 100°C for 36 h, and oxyhydroxide iron was obtained after washing with deionized water and ethanol; oxyhydroxide iron and carbon nanosheets were added to 50 mL of isopropanol at a mass ratio of 1:0.05, and after ultrasonic dispersion, the carbon / oxyhydroxide iron composite material was obtained by suction filtration; the carbon / oxyhydroxide iron composite material and the sulfur source were placed in a tubular furnace at a mass ratio of 1:2, and under the protection of an inert atmosphere, the temperature was raised to 500°C at a heating rate of 5°C / min, and calcined for 3 h to obtain a carbon / iron sulfide composite negative electrode material.

[0038] Figure 1 This is a scanning electron microscope image of the carbon / iron sulfide composite negative electrode material obtained in Example 1. It can be seen that the iron sulfide nanocubes are completely coated by the carbon nanosheets and are evenly dispersed inside the carbon nanosheets.

[0039] Figure 2 This is the X-ray diffraction diagram of the carbon / iron sulfide composite negative electrode material prepared in Example 1. It can be seen from the diagram that the obtained material only contains the diffraction peaks of iron sulfide and carbon, and does not contain other impurities.

[0040] The carbon / iron sulfide composite negative electrode material obtained in Example 1 was used as the working electrode and metallic sodium was used as the counter electrode to assemble into a button cell and test its cycle performance. Figure 3 As shown, at a current density of 0.05 A / g, the reversible capacity of the composite negative electrode material remained at 507 mAh / g after 60 cycles, and the first coulombic efficiency was 86.34%. Figure 4 The rate performance curve of the carbon / iron sulfide composite negative electrode material prepared in Example 1 of the present invention shows that the reversible capacities are 504.7, 484.3, 445.4, 364 and 207.4 mAh / g at 0.05, 0.1, 0.2, 0.5 and 1 A / g, respectively.

[0041] Example 2

[0042] 0.03 mol of ferric chloride hexahydrate was added to 80 mL of deionized water and stirred thoroughly to obtain solution A; solution A was then added to 150 mL of 3 mol / L potassium hydroxide solution and stirred continuously to obtain solution B; solution B was aged at 120°C for 48 h, and iron hydroxide was obtained after washing with deionized water and ethanol; iron hydroxide and carbon nanosheets were added to 80 mL of isopropanol at a mass ratio of 1:0.03, and after ultrasonic dispersion, a carbon / iron hydroxide composite material was obtained by filtration; the carbon / iron hydroxide composite material and a sulfur source were placed in a tubular furnace at a mass ratio of 1:1, and under the protection of an inert atmosphere, the temperature was raised to 600°C at a heating rate of 3°C / min, and calcined for 2 h to obtain a carbon / iron sulfide composite negative electrode material.

[0043] Example 3

[0044] 0.06 mol of ferric sulfate was added to 80 mL of deionized water and stirred thoroughly to obtain solution A; solution A was then added to 150 mL of 3 mol / L sodium hydroxide solution and stirred continuously to obtain solution B; solution B was aged at 110°C for 72 h, and oxyhydroxide iron was obtained after washing with deionized water and ethanol; oxyhydroxide iron and carbon nanosheets were added to 100 mL of isopropanol at a mass ratio of 1:0.03, and after ultrasonic dispersion, the carbon / oxyhydroxide iron composite material was obtained by suction filtration; the carbon / oxyhydroxide iron composite material and the sulfur source were placed in a tubular furnace at a mass ratio of 1:1.5, and under the protection of an inert atmosphere, the temperature was raised to 700°C at a heating rate of 3°C / min, and calcined for 2 h to obtain a carbon / iron sulfide composite negative electrode material.

[0045] Example 4

[0046] 0.1 mol of ferric chloride hexahydrate was added to 80 mL of deionized water and stirred thoroughly to obtain solution A; solution A was then added to 120 mL of 2 mol / L ammonia solution and stirred continuously to obtain solution B; solution B was aged at 80°C for 72 h, and oxyhydroxide iron was obtained after washing with deionized water and ethanol; oxyhydroxide iron and carbon nanosheets were added to 100 mL of isopropanol at a mass ratio of 1:0.03, and after ultrasonic dispersion, the carbon / oxyhydroxide iron composite material was obtained by suction filtration; the carbon / oxyhydroxide iron composite material and the sulfur source were placed in a tubular furnace at a mass ratio of 1:3, and under the protection of an inert atmosphere, the temperature was raised to 500°C at a heating rate of 8°C / min, and calcined for 4 h to obtain a carbon / iron sulfide composite negative electrode material.

[0047] Example 5

[0048] 0.02 mol of ferric chloride hexahydrate was added to 80 mL of deionized water and stirred thoroughly to obtain solution A; solution A was then added to 200 mL of 1 mol / L potassium hydroxide solution and stirred continuously to obtain solution B; solution B was aged at 100°C for 72 h, and oxyhydroxide iron was obtained after washing with deionized water and ethanol; oxyhydroxide iron and carbon nanosheets were added to 100 mL of ethanol at a mass ratio of 1:0.08, and after ultrasonic dispersion, the carbon / oxyhydroxide iron composite material was obtained by filtration; the carbon / oxyhydroxide iron composite material and the sulfur source were placed in a tubular furnace at a mass ratio of 1:2, and under the protection of an inert atmosphere, the temperature was raised to 600°C at a heating rate of 5°C / min, and calcined for 3 h to obtain a carbon / iron sulfide composite negative electrode material.

[0049] Comparative Example 1

[0050] The difference from Example 1 is that no carbon nanosheets are added. The rest is the same as Example 1 and will not be repeated here. The iron sulfide material obtained in Comparative Example 1 is used as the working electrode and sodium is used as the counter electrode to assemble a button cell and test its cycle performance. Figure 5 As shown, its first coulombic efficiency is 71.27%, and the reversible capacity remains at 65 mAh / g after 100 cycles at a current density of 0.05 A / g.

[0051] It can be seen that the method provided by the present invention can effectively alleviate the problems of unstable structure, strong volume expansion effect and poor cycle performance of single iron sulfide materials. Since the carbon nanosheets themselves have a stable structure, strong conductivity and good electrochemical performance, they can provide good support for iron sulfide materials. At the same time, the two-dimensional nanosheet structure also contains many active sites and sodium storage spaces, and constructs an interconnected conductive network, which significantly improves the electrochemical performance of the composite material. The self-supporting structure further constructed avoids the addition of binders and conductive carbon black, reduces the side reactions produced by non-conductive binders and large surface area conductive carbon black, thereby improving the first coulomb efficiency of the material, effectively improving the practical application value of the material, and the simple preparation process is suitable for industrial production.

[0052] Synthesis principle of the present invention:

[0053] The present invention adopts a simple chemical precipitation method to synthesize ferric hydroxide. During the reaction process, the iron source reacts with the alkaline solution to generate hydroxide precipitation. With the hydroxide as the core, as the aging reaction proceeds, the hydroxide continues to grow along the corresponding crystal plane to form ferric hydroxide particles.

[0054] After the iron oxyhydroxide and carbon nanosheets are mixed, the hydroxyl groups in the iron oxyhydroxide will react with the abundant hydrogen ions on the surface of the carbon nanosheets and connect to the surface of the carbon nanosheets through chemical bonds. At the same time, due to the two-dimensional structure of the carbon nanosheets, the nanoscale iron oxyhydroxide can be completely coated by the carbon nanosheets, and then the two can be composited by simple filtration.

Claims

1. A method for preparing a carbon / iron sulfide composite negative electrode material, characterized in that: The specific steps are as follows: Step 1, adding an iron source to deionized water and stirring the water sufficiently to completely dissolve the iron source to obtain a solution A; The iron source in step 1 includes one or more of ferric chloride hexahydrate, ferric nitrate nonahydrate, and ferrous sulfate; the ratio of the iron source to deionized water is: 0.01 -0.1 mol: 10-200 mL; Step 2: adding solution A to the alkaline aqueous solution and stirring continuously until fully mixed to obtain a mixed solution B; The alkaline aqueous solution in step 2 includes one or more of potassium hydroxide, sodium hydroxide, and ammonia water; the concentration of the alkaline aqueous solution is 1-10 mol / L, and the volume ratio of the alkaline aqueous solution to the deionized water in step 1 is 1:1; Step 3: aging the mixed solution B at high temperature, then washing the product with deionized water and ethanol, and drying to obtain iron oxyhydroxide; The high temperature in step 3 is 70-150°C and the aging time is 24-96 hours; Step 4: adding ferric oxyhydroxide to a carbon nanosheet solution dissolved in an organic solvent in proportion, dispersing uniformly by ultrasonication, and then filtering to obtain a carbon / ferric oxyhydroxide composite material; Step 5, placing the carbon / iron oxyhydroxide composite material and the sulfur source into a tubular furnace, and performing high-temperature carbonization under the protection of an inert atmosphere to obtain a carbon / iron sulfide composite negative electrode material.

2. The method for preparing the carbon / iron sulfide composite negative electrode material according to claim 1, characterized in that: In step 4, the mass ratio of iron oxyhydroxide to carbon nanosheets is 1:0.01-0.1; and the organic solvent is one or more of isopropanol, N,N-dimethylformamide, ethanol, and methanol.

3. The method for preparing the carbon / iron sulfide composite negative electrode material according to claim 1, characterized in that: In step 4, the preparation method of the carbon nanosheet is: using graphite paper as a working electrode, a platinum sheet as an inert electrode, 0.1-2 M sulfuric acid as an electrolyte, electrolysis at a voltage of 1-15 V, and after the reaction is completed, washing to neutrality to obtain a carbon nanosheet.

4. The method for preparing the carbon / iron sulfide composite negative electrode material according to claim 1, characterized in that: In step 5, the mass ratio of the carbon / iron oxyhydroxide composite material to the sulfur source is 1:0.5-5, and the sulfur source is one or more of thiourea, sulfur powder, and thioacetamide.

5. The method for preparing the carbon / iron sulfide composite negative electrode material according to claim 1, characterized in that: In step 5, the heating rate in the high-temperature carbonization is 2-10°C / min, the calcination time is 1-5h, and the constant temperature is 400-700°C.

6. A carbon / iron sulfide composite negative electrode material obtained by the preparation method according to any one of claims 1 to 5, wherein the carbon / iron sulfide composite negative electrode material is used in a sodium ion battery.

Citation Information

Patent Citations

  • Three-dimensional porous carbon-based selenide / iron sulfide composite material and application thereof in sodium ion battery

    CN117334907A

  • Preparation methods of iron-sulfur compound and preparation method of iron-sulfur compound composite material

    CN106745323A

  • Graphene oxide doped FeS composite nano material and preparation method thereof and application of graphene oxide doped FeS composite nano material

    CN110190263A